2014
DOI: 10.1515/ipc-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

FPGA Implementation of Decision Trees and Tree Ensembles for Character Recognition in Vivado Hls

Abstract: Abstract. Decision trees and decision tree ensembles are popular machine learning methods, used for classification and regression. In this paper, an FPGA implementation of decision trees and tree ensembles for letter and digit recognition in Vivado High-Level Synthesis is presented. Two publicly available datasets were used at both training and testing stages. Different optimizations for tree code and tree node layout in memory are considered. Classification accuracy, throughput and resource usage for differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…However they do not support GBDT and they apply their techniques only to simple case studies. Reference [15] proposes to use a high-level synthesis approach to design an FPGA accelerator. They focus on Random Forest, which is an ensemble technique that calculates the average value of several trees trained with different input data to generate a more accurate and robust final output.…”
Section: Related Workmentioning
confidence: 99%
“…However they do not support GBDT and they apply their techniques only to simple case studies. Reference [15] proposes to use a high-level synthesis approach to design an FPGA accelerator. They focus on Random Forest, which is an ensemble technique that calculates the average value of several trees trained with different input data to generate a more accurate and robust final output.…”
Section: Related Workmentioning
confidence: 99%
“…Kulaga et al [24] have proposed FPGA implementation of decision tree and its ensemble for letter and digit recognisition using Vivado High Level Synthesis tool. It is explained about Vivado HLS that it is one of the tool available for Xilinx FPGAs and Zynq SoC devices for synthesisation.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, the paper reported that the proposed implementation can reduce the consumed energy by 93.7% compared to a GPU implementation [13]. The authors in [15] designed a decision tree classifier to recognize letters and digits. Xilinx Zynq SoC is used by the authors as a target hardware platform and Vivado high level synthesis is used as a development tool with C/C++ synthesis.…”
Section: Related Workmentioning
confidence: 99%
“…Xilinx Zynq SoC is used by the authors as a target hardware platform and Vivado high level synthesis is used as a development tool with C/C++ synthesis. Authors verified the correctness of the generated HDL code using C/RTL co-simulation [15].…”
Section: Related Workmentioning
confidence: 99%